Biogas yield prospection from swine manure and placenta in real-scale systems on circular economy approach. (May 2020) - Soares, Clenoir Antonio; Viancelli, Aline; Michelon, William; Sbardelloto, Marina; Camargo, Aline F.; Vargas, Gean Delise L.P.; Fongaro, Gislaine; Treichel, Helen
Abstract: This study evaluated three biogas systems: i) biodigester 1 - without agitation system and fed with swine manure plus 1% crushed placenta; ii) biodigester 2 - without agitation system and fed only with swine manure; iii) biodigester 3 - with automated agitation system and fed only with swine manure. The biogas and methane production were determined by the biochemical potential of methane during one month of operation. The addition of 1% of swine placenta increased by 20% the production of biogas and methane. Agitation was fundamental to increase by 20% of the biogas produced in biodigester 3, which was fed only with swine waste. The results show the biogas production potential under different conditions, to be adopted according to each swine production unit, has been an interesting method of final disposal of remains of the production in swine maternities on circular economy approach. Highlights: High potential of biogas production. Co-digestion of swine manure and placenta. Circular economy approach in rural area.